The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1186/1471-2121-10-29
|View full text |Cite
|
Sign up to set email alerts
|

Horse bone marrow mesenchymal stem cells express embryo stem cell markers and show the ability for tenogenic differentiation by in vitro exposure to BMP-12

Abstract: Background: Mesenchymal stem cells (MSCs) have been recently investigated for their potential use in regenerative medicine. MSCs, in particular, have great potential, as in various reports they have shown pluripotency for differentiating into many different cell types. However, the ability of MSCs to differentiate into tendon cells in vitro has not been fully investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
138
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(156 citation statements)
references
References 53 publications
12
138
1
4
Order By: Relevance
“…JuncosaMelvin et al further showed that mechanical stimulation of MSCs-collagen sponges constructs significantly improved tendon repair in rabbit model (Juncosa-Melvin et al 2006). In vitro, MSCs have been successfully induced into tenocytes by exposure to growth factors BMP-12 (Violini et al 2009) or low-dose FGF-2 (Hankemeier et al 2005). Meanwhile, GDF-5 has also been reported to increase mRNA expression of Col I and SCX in MSCs which are believed to be the markers of tendon/ligament differentiation (Farng et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…JuncosaMelvin et al further showed that mechanical stimulation of MSCs-collagen sponges constructs significantly improved tendon repair in rabbit model (Juncosa-Melvin et al 2006). In vitro, MSCs have been successfully induced into tenocytes by exposure to growth factors BMP-12 (Violini et al 2009) or low-dose FGF-2 (Hankemeier et al 2005). Meanwhile, GDF-5 has also been reported to increase mRNA expression of Col I and SCX in MSCs which are believed to be the markers of tendon/ligament differentiation (Farng et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…When overused or subjected to sudden high strain, injuries such as inflammation, degeneration of the tendon might occur, which may eventually lead to rupture. However, probably because tenocytes are highly differentiated cells and have limited potential to replicate, the instinct healing ability of tendon is poor and replacement tissues are usually required for tendon regeneration Violini et al 2009). Recently, using adult bone marrow derived MSCs as seed cells to regenerate functional tendon attracted great interests with the promising use of MSCs in engineering tissue construction and transplantation without allograft rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Given there is currently no sufficiently effective pharmaceutical-based therapy, the use of more potent biological molecules was proposed as an alternative strategy. increases revascularisation of repairing tendon tissue, improving overall healing [169]; plateletderived growth factor (PDGF) has beneficial effects on the functional repair of tendon tissue in the canine model, increasing tendon glide, but not mechanical properties, over a 42 day period [170]; basic fibroblast growth factor (bFGF) stimulates both MSC proliferation and differentiation towards tenogenic lineage, leading to increased expression of tendon specific ECM proteins and increased collagen production from cells [171]; bone morphogenic protein 12 (BMP-12), also referred to as growth differentiation factor 7 (GDF-7) induces both in vitro and in vivo tenogenesis of MSCs in both human and equine cells [172][173][174]; BMP-13 (GDF-6) induces an increase in the expression of tendon specific proteins in rat MSCs along with increasing the characteristic wave like pattern found in tendon histological samples after 14 days implantation in a rat Achilles defect model [175]; BMP-14 (GDF-5) reduces adhesion formation between tendons and surrounding tissues, improving overall function and recovery [176]; early growth response protein 1 (EGR1) directs tendon differentiation in rat MSCs and improve tendon healing in a rat Achilles tendon injury model [177]; and transforming growth factor-β (TGF-β) is highly influential in the recruitment and maintenance of TC progenitor cells during injury [178]. While these growth factors have demonstrated efficacy, as assessed by increased cellular migration, matrix production and matrix mechanical properties over a short period of time (up to around 8 weeks), little difference has been documented in long term tissue integration, matrix composition and overall tissue strength over control groups [177,178].…”
Section: Delivery Of Pharmaceutical Agentsmentioning
confidence: 99%
“…RNA was then converted to cDNA using RevertAid H Minus M-MLV RT reverse transcriptase (Fermentas, Burlington, Ontario, Canada). All RT-qPCR reactions were carried out as previously described (Violini et al 2009). Dissociation curve analysis was run to ensure the absence of non specific PCR products.…”
Section: Stem Cell Marker Expressionmentioning
confidence: 99%
“…Specific transcription factors define mesenchymal stromal characteristics involved in maintaining the undifferentiated stem cell pattern required for selfrenewal (Greco et al 2007) and are expressed by different animal tissue-derived mesenchymal stromal cells such as horse bone marrow stem cells (Violini et al 2009) and rat amniotic membrane stem cells (Marcus et al 2008); Moreover human amnion stromal cells were reported to express cell surface markers such as octamer-binding transcription factor Oct4, Nanog (Toda et al 2007), CD105 but not hematopoietic markers such as CD34 (In't Anker et al 2004;Parolini et al 2008). …”
Section: Introductionmentioning
confidence: 99%